A note on polynomially-solvable cases of common due date early-tardy scheduling with release dates - Valente,Jorge M. S. (2004)
In this paper we consider the single machine scheduling problem with integer release dates and the objective of minimising the sum of deviations of jobs' completion times from a common integer due date. We present an efficient polynomial algorithm for the unit processing time case. We also show how to calculate in polynomial time the minimum non-restrictive due date for the general case.